A COMPARATIVE ANALYSIS OF THE APPLICATION OF JOINT TENANCY IN THE ADMINISTRATION OF REAL PROPERTY IN MALAYSIA, SINGAPORE, AND AUSTRALIA - Arshad, Azhani; Mohd Yusoff, Rahmawati; Mat Ali, Syuhaeda Ani; Halim, Akmal Hidayah; Adnan, Nur Akmal (PLANNING MALAYSIA, 2023)
Joint tenancy has been applied when one of the joint tenants dies; the deceased's left portion must be given to the surviving joint tenant. The National Land Code (Act 828) acknowledges the concept of joint ownership in form of tenancy in common while the right of survivorship was only acknowledged in the National Land Code (Penang and Malacca Titles) Act 1963. Therefore, the research aims to explore the concept of joint tenancy and the existing laws governing the joint ownership in Malaysia. This research is based on the qualitative research and analysis of the primary and secondary materials through the governing statutes and reported cases. The research also explores the practice of joint tenancy in Singapore and Australia for comparative analysis. It is predicated that the application of joint tenancy would give the advantage to the surviving joint tenant towards the full enjoyment of the property.